Antibacterial Activity Test of Sapodilia Leaf Extract (Manilkara zapota) Against Escherichia coli Bacteria - Rahmawati, Rizka Dwi; Faisal; Ramadhan, Majida (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Antibacterial refers to a substance or compound capable of hindering bacterial growth or eradicating bacteria by affecting the permeability of harmful microbes, particularly those harmful to humans. Leaves from the sapodilla tree (Manilkara zapota) contain secondary metabolites like tannins, flavonoids and saponins. The goal of this research is to evaluate the antibacterial properties of sapodilla leaf extract in slowing down the proliferation of Escherichia coli bacteria and to identify the concentration of sapodilla leaf extract that effectively inhibits the growth of Escherichia coli. The investigation employed the well diffusion technique with three repetitions. Data analysis was conducted using the One Way ANOVA test. Findings in this study indicated that the sample or treatment displayed a significance value las than 0,05, suggesting a notable difference among sample types in relation to the diameter of the clear zone, and that the concentration also showed a significance value less than 0,05, indicating a significant difference related to the concentration on the results of the clear zone diameter. The findings from this studys suggest that the greatest antibacterial efficacy was observed at concentration of 100%.